Regulating the electronic structure of MoO2/Mo2C/C by heterostructure and oxygen vacancies for boosting lithium storage kinetics. Issue 33 (4th August 2022) - Guo, Donglei; Yang, Mengke; Wang, Fang; Cheng, Yihua; Zhang, Anqi; Liu, Guilong; Wu, Naiteng; Cao, Ang; Mi, Hongyu; Liu, Xianming
Abstract : The intrinsic electronic conductivity and Li-ion diffusion kinetics of MoO2 /Mo2 C/C were improved by the heterostructure and oxygen vacancies. Abstract : The electronic structure regulation of electrode materials can improve the ion/electron kinetics, which is beneficial to the cyclic performance and rate capability for lithium ion batteries (LIBs). Herein, we propose a facile strategy to achieve a MoO2 /Mo2 C/C heterostructure with abundant oxygen vacancies. Density functional theory calculations indicate that the heterostructure of MoO2 /Mo2 C/C can significantly promote the Li + /charge transfer and reduce the Li adsorption energy, and the abundant oxygen vacancies in MoO2 /Mo2 C/C can improve the intrinsic electronic conductivity and reduce the Li + diffusion barrier. Benefiting from the multiscale coordinated regulation, the obtained MoO2 /Mo2 C/C film exhibits outstanding high rate capability (454.7 mA h g −1 at 5 A g −1 ) and remarkable cyclic performance (retaining 569 mA h g −1 over 1000 cycles at 2 A g −1 ). The insightful findings in this study can shed light on the behavior of the electron/ion structure regulation by the heterostructure and oxygen vacancies, which can guide future studies on designing other electrode materials with high-performance lithium-ion storage.